« Whether it be dampnation for a man to kill hym self » (1578) : trouble dans la foi dans les documents du fonds Add. MS27632 - Irène Vilquin (Miranda: Revue Pluridisciplinaire du Monde Anglophone, 2025)
Although regularly mentioned in suicide studies, the anonymous manuscript “Whether it be dampnation for a man to kill hym self” (1578) – often attributed to John Harington – was seldom regarded as a textual production in its own right. The document, however, is supported by a rich literary and theological heritage. The text breaks from Augustine’s tradition of reprobation, modifies Elizabethan readings of Biblical and Classical suicides, and thus appears to echo the premises of a counter-speech on suicidal acts. The present article offers to compare the manuscript with contemporary texts in order to better comprehend how important dialogical forms were in the creation and circulation of heterodox ideas in early modern England.